RICE PRODUCTIVITY ESTIMATES BASED ON CLIMATE ANOMALY AND LAND VEGETATION INDEX (NDVI) - Oktalia Dilarosa, Indah
Rice is the staple food of Indonesia, especially in Indramayu that is a national granary areas. The phenomenon of climate change is affecting rainfall patterns change in Indramayu, it may cause the failure of farmers and lead to a decrease in productivity of rice. Calendar planting is one adaptation strategy for farmers to overcome crop failure, productivity forecast information is also needed to complete the planting calendar. It is, therefore interesting to do the calculation of the forecast productivity of rice based on climate anomaly and land vegetation index in Indramayu. In this study, the method of multiple linear regression analysis is used to see the relationship between the rice produktivity and parameters of climate anomaly and land vegetation index. In addition, testing the simulation results rice productivity by using observation data is used to find the accuracy between real data and simulation data. The data used in this research are anomalies of rainfall, maximum and minimum temperature, Nino 3.4 SST anomaly, anomalous Southern Oscillation Index (SOI), and the index Normalized Difference Vegetation Index (NDVI). The simulation results of multiple linear regression analysis showed that in each subdistrict has different parameter influence on the productivity of rice. Pasekan Subdistrict showed that Nino 3.4 SST anomaly, SOI anomaly, and rainfall has a the strong influence to rice productivity based on significant results which is closer to confidence level of 0.05. Furthermore, Kroya Subdistrict showed climate anomalies parameters that has strong influence in this area are rainfall and index of Growing Degree Day (GDD). Based on simulation results with observational data, it is obtained deviation value of 2.1911 for the Pasekan subdistrict and 2.9440 for the Kroya subdistrict. On the predicted results for productivity of rice in 2016, Pasekan produced rice for 66.53 Kw / Ha and the Kroya produced rice for 44.015 Kw / Ha.